Effect of splenic sequestration of erythrocytes on splenic clearance function and susceptibility to septic peritonitis. - Grover, G J (1982)
The effect of splenic sequestration of erythrocytes (RBC) on splenic clearance function and susceptibility to septic peritonitis was studied. Homologous RBC were treated with 20 mM phenylhydrazine hydrochloride in vitro and injected into rats at doses of 5, 15, 75, and 150 mg of hemoglobin per 100 g. Splenic 93, 23, and 13% of the injected dose, respectively, whereas less than 2.1% of the same doses of washed RBC were localized in the spleen. The total quantity of phenylhydrazine-treated RBC sequestered by the spleen was similar for the three larger doses (40 to 45 mg of hemoglobin per g of tissue), indicating that this is the capacity of the spleen to take up this type of RBC in 234 h. The phenylhydrazine-treated RBC in doses of 15, 75, and 150 mg of hemoglobin per 100 g depressed the clearance rate and splenic localization of a test dose of phenylhydrazine-treated RBC, whereas splenic clearance function was unchanged after a dose of 5 mg of hemoglobin per 100 g. Splenectomy or injection of doses of phenylhydrazine-treated RBC which depressed splenic clearance function increased the susceptibility to septic peritonitis induced by cecal ligation and puncture. After thermal injury, splenic clearance function was found to be depressed. Also, splenic localization of RBC 24 h after thermal injury was found to be approximately equal to that after injection of the doses of phenylhydrazine-treated RBC which depressed splenic clearance function. It is concluded that splenic sequestration of RBC can depress splenic clearance function and increase susceptibility to peritonitis, and that this may be one mechanism for the increased susceptibility to infection seen after thermal injury.